Educa????o n??o formal: um olhar sobre uma experi??ncia em Campinas - SP - Morais, Paula Renata Bassan (2012)
This research had the objective to study non formal education in an institution of Sistema S, the Servi??o Nacional de Aprendizagem Comercial (Senac), which is a private entity that develops social politics orientated to learn ship, culture and welfare. We wonder if non formal education is an alternative that shows them paths, they will be able to create conditions to transform and act in their social reality. We started our study performing field research a brief mapping of the associations in Campinas and Valinhos, both located in S??o Paulo state, and non formal education in a particular social project named Cemoa Sem Limites. It was developed by a partnership between Senac Campinas and Valinhos city hall. The research presents a study application of a questionnaire about some participants of Projeto Cemoa Sem Limites. After analyzing the general profile of the institution and the attended clientele, some participants were selected for the oral history register. We analyses the participants behavior before attending the project and during their participation, in order to understand the non formal education role in the individuals formation. The research material is analyzed following the literature presented in Chapter 1.